Subjectivity, identity, and self-transformation: An anthropological approach to travel encounters in India - Bastos, Cecilia (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2024)
This article focuses on the potential of travelling which spiritual pilgrims to India experience as opportunity for self transformation. In this process, travelling offers contact with “otherness” and a sense of critical distance from everyday values and ideas. The article explores symbolic meanings of travel as a secular ritual involving ruptures with the ordinary. Seeing them as a driving force behind the creation of relationships between different traditions, this article looks at encounters from an anthropological perspective. Based on my empirical research on the intentions of foreign travellers in India and by studying their motivations and searches, I argue that such travels can be understood as a means for travellers not only to find others but also to encounter themselves.